ANALYSIS OF FACTORS INFLUENCING EMPLOYEE PERFORMANCE CASE STUDY AT BULOG PERUM REGIONAL DIVISION SOUTHEAST SULAWESI - Wahyudi; H Djabir Hamzah; Hj Nurdjanah Hamid (Scientia Integritas Utama, 2023)
This study aims to analyze; 1). Effect of Financial Compensation on Employee Satisfaction. 2). The Effect of Financial Compensation on Employee Motivation, 3). Effect of Financial Compensation on Employee Performance, 4). Effect of Non-Financial Compensation on Employee Satisfaction, 5). Effect of Non-Financial Compensation on Employee Motivation, 6). Effect of Non-Financial Compensation on Employee Performance, 7). Effect of Satisfaction on Employee Motivation, 8). Influence of Motivation on Employee Performance The analytical method used is Parth Analysis. The research results show the following findings; 1). Giving financial compensation and non-financial compensation in general gives a very good assessment, as well as in the path analysis has a significant influence on satisfaction. Even though the path coefficient between financial compensation and satisfaction gives a negative or non-unidirectional path relationship. However, the empirical phenomenon is that financial compensation for employees is very adequate or at a sufficient level of welfare. 2). Financial compensation has a significant influence on motivation, and the path coefficient relationship is positive or unidirectional so that any additional financial compensation will increase employee motivation. 3). Influence between financial compensation variables and performance, in this study proves that there is no significant effect, but there is a unidirectional relationship or a positive relationship. This means that if financial compensation is increased, performance will also increase even though this increase does not have a real impact on employee performance. 4). There is a significant influence between non-financial compensation on the level of employee satisfaction, and the path coefficient has a positive or unidirectional relationship. 5). Non-financial compensation has a significant influence on employee motivation, and the path coefficient has a positive or unidirectional relationship. 6). Non-financial compensation has a significant effect on performance but the path coefficient of the relationship gives a negative value or is not unidirectional. 7). Satisfaction factors are generally considered very good, and has a significant effect on motivation and the path coefficient has a positive or unidirectional relationship. Means this variable can measure employee motivation. 8). Motivational factors have a significant influence on employee performance and the value of the regression coefficient is positive or unidirectional, and this variable can measure employee performance.